High prevalence of vitamin D deficiency in school children in Jammu: a whistle blower - Kaur, Harleen; Bhatia, Amarjeet Singh (International Journal of Research in Medical Sciences, 2019)
Background: Vitamin D deficiency prevails in epidemic proportions among school going children in India, but there is scarcity of searchable data on vitamin D status in school children in Jammu and Kashmir; hence we have assessed the vitamin D status in school going children attending outpatient department in a tertiary care hospital Jammu. Methods: The study was conducted in the department of Biochemistry Government Medical College Jammu during June to December, 2018 and after obtaining informed consent, a total of 104 school going children between the age group of 6 years to 12 years, attending SMGS Hospital Jammu were screened for their vitamin D (25 OH-D) status by using Abbott architect chemiluminescent micro particle immunoassay. Results: Out of a total of 104 school going children screened in the study, 91 (87.5%) were found to be having insufficient vitamin D levels in their blood (<30ngm/dl) whereas 63 (60.5%) children showed severe deficiency with vitamin D levels below 20ngm/dl. Conclusions: Despite of abundant sunshine throughout the year and also with the consideration that people of this region are well off economically and can afford good nutrition, the results of our study revealing high prevalence of Vitamin D deficiency in school going children can be taken as a whistle blower for the health policy makers of the region.